Pengaruh Ketimpangan Pendapatan, Inflasi, dan Investasi Terhadap Pertumbuhan Ekonomi di Pulau Sumatera - Aditya Ferino; Idris (Universitas Negeri Padang, 2024)
To what extent do different variables influence economic development in Sumatra is the overarching goal of this research. First, there is the issue of income disparity; second, inflation; and third, the impact of investment on Sumatra's economic development. The quantitative methodology of this research is based on the use of secondary data collected from ten provinces on the island of Sumatra using panel data. This data mixes time series data from 2019 to 2023 with cross-sectional data. In this study, panel data analysis is used. Investment significantly reduces economic growth, although income disparity and investment both have negligible effects, according to the research.